Breastfeeding And Infant Care in the Context of HIV/AIDS - Richter, Linda; Griesel, Dev (PINS-Psychology in Society, 2026)
In many parts of the world, but especially in resource-poor countries, the HIV-epidemic is spreading most rapidly amongst young women of child-bearing age (Abdool Karim, Abdool Karim, Singh, Short & Ngxongo, 1992). More than 90% of HIV-1 infection in children occurs by vertical transmission, thus infection in women poses the major risk of infection for children The estimated rate of vertical transmission varies, with the lowest rates being reported in Europe (15-20%) and the highest rates in Africa (25-35%) (Newell & Gibb, 1995; Bobst, Coovadia, Coutsoudis & Moodley, 1996). In itself, the relationship between maternal Infection and child vulnerability is fused into the gendered discourse about HIV/AIDS prevention, in which women are constructed and targeted as agents of both cause and potential modification of transmission (Grosz, 1994). The current dilemmas about feeding guidelines in the context of vertical transmission risk relate also to this fusion and are profoundly enacted around the matter of choice of feeding methods alloted to women in current HIV infant feeding policy.